LAW ENFORCEMENT AGAINST HEALTH PROTOCOL COVID-19 VIOLATIONS IN INDONESIA: A Case Study of Decision Number: 173/PID.SUS/2021/PT.DKI - Muslihuddin, Mochammad; Yahman, Dr. Yahman (jfpublisher, 2022)
The Corona Virus, or Covid-19, has spread throughout Indonesia since early 2019. This virus initially emerged in connection with an animal market in Wuhan, China. The spread of Covid-19 caused panic and anxiety among people worldwide. Cooperation from all communities is essential to prevent the virus from spreading further. In response, the Police in each region enforce rules based on the Chief of Police's recommendations. Law enforcement officers are directly involved in preventing the transmission of Covid-19. In carrying out their duties, the Police work in synergy with relevant agencies, the Indonesian National Army (TNI), religious leaders, and all levels of society. This research aims to examine police policies and government enforcement rules in preventing virus transmission. The study analyzes government regulations, police chief policies, and related legal sources. The findings are based on police legal regulations and government laws, implemented according to their roles and responsibilities. Law enforcement takes an active approach by promoting values and norms within communities, ensuring compliance, and addressing violations during their duties. These regulations still require discipline and transparency in handling information related to protocol violations during the pandemic.